Chemistry students' aversion to the use of slides in the classroom (Revista Contexto & Educação, 2026)
This article presents the findings of a qualitative study that investigated the perceptions of undergraduate Chemistry teacher education students from a public university in the countryside of São Paulo state regarding the use of slides as an instructional resource, analyzing their current status as an educational technology. The exploratory investigation utilized interviews and questionnaires administered to 14 students, with the analysis grounded in the Discursive Textual Analysis (DTA). The results reveal that, although slides are widely used by instructors, students no longer perceive them as technological tools, instead associating them with conventional, minimally interactive, and unstimulating pedagogical practices. This perception indicates a shift in the criteria for recognizing what is understood as technological, marked by the obsolescence attributed to resources incorporated into academic daily life. The saturation of slide usage and their consequent trivialization in the university environment highlights a process of naturalization of technologies that, upon losing their innovative character, cease to be problematized in their pedagogical and cultural dimensions. The study points out that the mere use of Digital Information and Communication Technologies (DICT)  does not, by itself, guarantee innovation in the teaching-learning process. It therefore becomes necessary to consider didactic intentionality, the formative context, and active listening to students as central elements for the re-signification of the resources used. The research contributes to the debate on the critical use of technology in education, highlighting the urgency of planned pedagogical practices that overcome the mere digitalization of traditional methods and promote meaningful and favor meaningful learning.
Keywords: Technology; Chemistry Teaching; Academic Motivation